Wastewater Processing Technology Opportunities for Palm Oil Mill Effluent as a Raw Material for Renewable Bioenergy - Andri Gumilar; Mindriany Syafila; Marisa Handajani; Ilham Anggamulia; Syarif Hidayat (Journal of Engineering and Technological Sciences, 2022)
The effect of pH on the formation of hydrogen and ethanol using POME as the substrate has not been widely studied. Indonesia, which is the largest producer of palm oil, has a high potential for the utilization of this liquid waste as a substrate for the formation of hydrogen and ethanol. This study determined the optimum hydrogen and ethanol production conditions by controlling pH. POME was used as substrate in an anaerobic reactor and operated in feed batch mode for 72 hours. Mixed culture anaerobic bacteria as biomass were used in the reactor. The pH of the reactor was adjusted to 4.5, 5.5, 6.5, and 7.5 using NaOH 0.1 N and HCl 0.1 N. The reactor’s performance was investigated by measuring hydrogen production, ethanol production, and volatile fatty acid product. It was found that with an initial pH of 5.5, hydrogen production was higher than for the other pH conditions, at about 14.7% v/v. In contrast, the most increased ethanol production occurred in the reactor with an initial pH of 6.5 with a concentration of 347.7 mg/L. Based on the results of this study, the right pH setting can optimize hydrogen and ethanol production.